TOWARDS A VIABLE LANGUAGE OF HUMAN RIGHTS ACTIVISM IN NIGERIA - Temitope Abiodun Balogun (European Scientific Journal, ESJ, 2012)
This paper explores the possibilities of achieving a viable language of human rights activism in contemporary Nigeria. It argues that the style of language of human right activists is predominantly violent, harsh and incapable of achieving the crucial goals and visions of human right activism in Nigeria: The methodology is analytical and empirical. In its analytical approach, it discusses the meaning and roles of language in societal cohesion. Its empirical character derives from the collation and analysis of data of some selected speeches of Nigerian activists on violation of citizens’ human rights, conflict resolution and effective democratization process. Finally, while recognizing the pivotal role of human rights activism in contemporary Nigeria, the paper emphasizes the need to inject humane linguistic items that reflect a measure of respect, integrity and modesty in the language style of human rights activists. This is necessary in order to achieve dialogue, understanding and consensus on controversial issues among human rights activists, government functionaries and stakeholders in the Nigerian state. This is the only viable path to sustainable democracy and human development.